Virtual generative BIM workspace for maximising AEC conceptual design innovation: A paradigm of future opportunities. Issue 1 (5th January 2015) - Abrishami, Sepehr; Goulding, Jack; Pour Rahimian, Farzad; Ganah, Abdul
Abstract : Purpose: – The purpose of this paper is to find optimal solutions for conceptual design automation, which can be integrated with Building Information Modelling (BIM) support for construction automation. Problems relating ostensibly to failures in computational support for the conceptual design stage are well-documented in extant literature. These failures are multifarious and significant, with several deficiencies being acknowledged in the Architecture, Engineering, and Construction (AEC) industry. Whilst acknowledging this, extant literature has highlighted the importance of computational design in the AEC industry; and failures in this area include the need to strengthen the congruent links and support mechanisms in order to exploit the opportunities presented by new computational design methods. Given this, it is postulated that the application of generative design could enhance the design experience by assisting designers with the iterative generation of alternatives and parameterisation (change management) processes. Moreover, as BIM applications are increasingly providing comprehensive support for modelling and management, then additional synergies could be examined for further exploitation. Design/methodology/approach: – This paper focusses on the potential for developing an interactive BIM environment that purposefully adopts generative design as a method of computational design for the early design stages. This research facilitates the automation of the conceptual architectural design process, using BIM as the central conduit for enhancing the integration of the whole building design process (including design interfaces). This approach is designed to improve designers' cognition and collaboration during the conceptual architectural design process. Findings: – This paper evaluates the existing methods and decision support mechanisms, and it introduces the potential of combining different concepts into a single environment (generative design/BIM). Originality/value: – This research is novel, in that it critically appraises virtual generative workspaces using BIM as the central conduit. The outcome and intervention of this research forms a theoretical basis for the development of a "proof of concept" prototype, which actively engages generative design into a single dynamic BIM environment to support the early conceptual design process.